Statistical Optimization of Culture Conditions and Characterization for Ligninolytic Enzymes Produced from Rhizopus Sp. Using Prickly Palm Cactus Husk. Issue 1 (2nd January 2017) - dos Santos, Tamires Carvalho; de Brito, Aila Riany; Bonomo, Renata Cristina Ferreira; Pires, Aureliano José Vieira; Aguiar-Oliveira, Elizama; Silva, Tatielle Pereira; Franco, Marcelo
Abstract : Dry prickly palm cactus ( Nopalea cochenillifera ) husk was investigated as a substrate for Rhizopus sp. cultivation in the solid state, aiming at the production of laccase ( Lac ), lignin peroxidase ( LiP ), and manganese peroxidase ( MnP ). The optimization of fermentation was evaluated by an experimental design and it was obtained, for each enzyme, maximum productivities (U g −1 h −1 ) of: 0.085 ± 0.02 ( MnP ), 0.066 ± 0.001 ( LiP ), and 0.023 ± 2.3.10 −4 ( Lac ), at the conditions of 10 g of substrate, 72 h of fermentation, aw = 0.865, and 30°C. The enzymes thermal and pH stabilities were evaluated and it was observed better results at temperatures no higher than 60°C and pH of 5.0; in addition, the storage of these enzymes was better at − 25°C than at 4°C. Since the prickly palm cactus is an agricultural substrate and specially because of its low cost, it is important to propose different applications for it as, for example, an alternative substrate for biotechnological processes.